Promoting Islamic Private Equity Fund As An Ideal Financial Intermediary Institution - Akbar, Nashr; Haeikaly, Muhamad (IKONOMIKA, 2017)
The existence of financial intermediation institution is quite necessary to support the economic activity. It serves both surplus unit and deficit unit to meet their wants whereby the former wants to invest his money in the lack of skill, while the latter wants to develop their businesses but does not have adequate capital. Bank institution is the most common institution serving the people’s need of financial intermediation. However, bank has several weaknesses that may harm and hamper the economic development. This paper aims to explore the weaknesses of banks as financial intermediary institutions and then promote Islamic Private Equity Fund as alternative. The result showed that the weaknesses of banks are: 1) fractional reserve banking, 2) fiat money, 3) debt-based investment, 4) risk averse. Furthermore, the study also found that Islamic Private Equity Fund can serve as an ideal financial intermediary institution due to some strengths: 1) no fractional reserve banking, 2) equity-based investment and 3) risk taker